Strategy For Developing Small And Medium Enterprises With The Canvas Method In Seaweeds Processing - Kilbaren, Nurhalizah; Rawi, Rais Dera Pua; Mufrihah, Evi (Implikasi: Jurnal Manajemen Sumber Daya Manusia, 2024)
UKM Arar Berdikari is a business that operates in the culinary sector using seaweed as its basic ingredient. This research aims to determine the development of the Arar Berdikari UKM business and to determine the Arar Berdikari UKM model strategy using the Business Model Canvas. This research uses descriptive qualitative methods, the data used in this research is from interviews with informants and field observations. The research results show that 9 BMC blocks in Arar Berdikari UKM are Customer Segment, maintaining and strengthening relationships with existing customers. Value Proposition, offering value through the quality and authenticity of the seaweed taste. Channels, has quite good and effective channels with a distribution system. Customer Relationship, providing customer service and prioritizing a friendly and loyal attitude towards customers. Revenue Streams, has a revenue stream originating from the sale of processed seaweed products. Key Resources, has employees, production sites and production equipment. Key Activities, has two main activities, namely production activities and marketing activities. Key Partnership, has supply partners consisting of local seaweed farmers in Arar village. Cost Structure, UKM Arar Berdikari can optimize all costs to keep them under control.